Increased incidence of distal humeral fracture surgery and decreased incidence of respective corrective osteotomy among Finns aged 0 to 18 years between 1987 and 2016: A population-based study. (August 2019) - Salonen, A.; Niemi, S. T.; Kannus, P.; Laitakari, E.; Mattila, V. M.
Abstract: Purpose: Previous studies on paediatric and adolescent distal humeral fractures have reported an increase in surgical treatment activity. This increase could be hypothesized to reduce the incidence of corrective osteotomies. The aim of this study was to determine the incidence and trends of the primary surgical treatment of distal humeral fractures and corrective osteotomies in children and adolescents. Methods: All Finns 18 years of age or younger who underwent treatment for distal humeral fracture between 1987 and 2016 were included in this population-based study. Surgical treatment data were obtained from the National Hospital Discharge Register of Finland. In calculating annual surgery incidence rates, the annual mid-year populations were obtained from the Official Statistics Finland. Surgical treatment was categorized into four groups; reposition and casting, osteosynthesis, external fixation and corrective osteotomy. Results: During the 30-year study period, 9017 surgical procedures were performed in Finland with the primary or secondary diagnosis code being a distal humeral fracture. Of these, 6961 (77.2%) were osteosynthesis and the incidence of osteosynthesis (per 100 000 person-years) increased fourfold from 8.2 in 1987 to 34.1 in 2016. In the same 30-year study period, the total number of corrective osteotomies was low (151) with annual variation from one to 16. The incidence of corrective osteotomies (per 100 000 person-years) decreased sevenfold from 0.7 to 0.1. Conclusion: The incidence of surgical treatment with osteosynthesis in distal humeral fractures increased fourfold in Finland between 1987 and 2016. During the same time period, the number of corrective osteotomies diminished significantly. Level of Evidence: IV